Histomorphological Study of the Ovaries and Follicles Growth in Adult Female Albino Rats - Saif M. Haibet (Journal of Global Pharma Technology, 2019)
The Ovary plays a vital role in the reproductive process and this study was carried out in order to investigate the structure of ovaries of the female mature rat Ovaries were obtained by direct incision on the abdominal cavity and were then divided into two sections and fixed in buffered formalin. The sections (5-7 μm) were cut in paraffin blocks, stained with Mayer’s haematoxylin stain, periodic acid Schiff (PAS) technique. In histological examinations it was composed of two main zones, cortex and medulla. The surfaces of the ovaries were wavy and lined by simple cuboidal or columnar epithelium. The tunica albuginea consisted of connective tissue fibres. There were connective tissue cells in the cortex, as well as interstitial cells containing. Primordial, primary, secondary, tertiary follicles, corpus luteum and atretic follicles were seen in the cortex of ovaries. Mean diameters of these follicles varied between 80 and 1600 μm. Medulla consisted of loose connective tissue which contained blood and lymph vessels of varying sizes. The diameter of ovarian follicles in the cortex was measured as primordial 36.5±1.31µm, primary single layer 60.58±2.68µm, primary multi-layer 167.84±5.59µm, secondary with C-shaped antrum 193.83 ± 75.71 µm and graafian 389.62±9.55mm.